Analisis Determinan yang Mempengaruhi Tarif Riil Rumah Sakit pada Pelayanan Hemodialisa - Swandayana, Putu Gede Wawan; Menap, Menap; Sismulyanto, Sismulyanto; Putra, Made Mahaguna (Journal of Telenursing (JOTING), 2023)
This research aims to determine the determinant factors influencing the accurate rates for hemodialysis services at the Regional General Hospital of West Nusa Tenggara Province in 2021-2022. The method used is explanatory analysis with a quantitative approach. The research results show that the factors of patient condition, service activities, infrastructure resources, and type of dialyzer have a significant effect on the accurate hospital rates for hemodialysis services at the Regional General Hospital of West Nusa Tenggara Province in 2021-2022. In conclusion, the type of dialyzer factor has the most significant influence on the formation of accurate rates for Hemodialysis services in NTB Provincial Regional Hospitals in 2021-2022. Keywords: Hemodialysis, Services, Financing, Hospital